Establishing irrigation potential of a hillside aquifer in the African highlands - Tilahun, Seifu A.; Yilak, Debebe L.; Schmitter, Petra S.; Zimale, Fasikaw A.; Langan, Simon J.; Barron, Jennie; Parlange, Jean-Yves; Steenhuis, Tammo S. (Wiley, 2020)
Feeding 9 billion people in 2050 will require sustainable development of all water resources, both surface and subsurface. Yet, little is known about the irrigation potential of hillside shallow aquifers in many highland settings in sub-Saharan Africa that are being considered for providing irrigation water during the dry monsoon phase for smallholder farmers. Information on the shallow groundwater being available in space and time on sloping lands might aid in increasing food production in the dry monsoon phase. Therefore, the research objective of this work is to estimate potential groundwater storage as a potential source of irrigation water for hillside aquifers where lateral subsurface flow is dominant. The research was carried out in the Robit Bata experimental watershed in the Lake Tana basin which is typical of many undulating watersheds in the Ethiopian highlands. Farmers have excavated more than 300 hand dug wells for irrigation. We used 42 of these wells to monitor water table fluctuation from April 16, 2014 to December 2015. Precipitation and runoff data were recorded for the same period. The temporal groundwater storage was estimated using two methods: one based on the water balance with rainfall as input and baseflow and evaporative losses leaving the watershed as outputs; the second based on the observed rise and fall of water levels in wells. We found that maximum groundwater storage was at the end of the rain phase in September after which it decreased linearly until the middle of December due to short groundwater retention times. In the remaining part of the dry season period, only wells located close to faults contained water. Thus, without additional water sources, sloping lands can only be used for significant irrigation inputs during the first 3 months out of the 8 months long dry season.